Impact of physical therapy on the mobility, activity and independence of patients with stroke and total aphasia - Sybiriakin, Yaroslav; Balazh, Mariia (Journal of Education, Health and Sport, 2022)
The purpose of the study. To assess the effectiveness of physical therapy measures on the mobility, activity and independence indexes of patients with acute cerebrovascular accident and total aphasia at the inpatient stage of treatment. Materials and methods. The study involved 62 patients after acute cerebrovascular accident with sensorimotor aphasia, who were divided into 2 groups: an intervention group, n=32, and a comparison group, n=30. Patients in both groups received standardized drug therapy and rehabilitation measures that included physical therapy, occupational therapy, and speech and language therapy. Results. During the initial examination, the Rivermead Mobility Index and the Barthel Index indicated the complete inability of patients to independently perform any voluntary movements and their complete dependence in Activities of Daily Living. At the final examination, there was a statistically significant improvement (p<0.05) in the Barthel Index and the Rivermead Mobility Index in both groups, but the intervention group had a higher proportion of patients able to perform targeted activities independently. According to the Barthel Index, the proportion of patients who improved the degree of independence in Activities of Daily Living in the intervention group was 53.1%, while in the comparison group it was 13.3% (p=0.001). Conclusions. Application of the developed algorithm of physical therapy measures at the inpatient stage of treatment contributed to a more significant improvement in mobility and independence of patients with stroke and sensorimotor aphasia, compared to the standard approach. The obtained data confirm the necessity of application a special approach to the management of the physical therapy process in patients with sensorimotor aphasia caused by acute cerebrovascular accident.